Flood Mitigation of Peatlands on Oil Palm Plantation Based on HEC-RAS 2D Model - Lydiasari, Henny; Santoso, Heri (Jurnal Penelitian Kelapa Sawit, 2022)
The development of oil palm plantations on peat swamp land is increasingly widespread and is the biggest challenge in its management. Severely obstructed drainage is one of the limiting factors affecting the hydrological conditions of the land. This hydrological study was conducted in one of the oil palm plantations in Muara Batang Toru districts, North Sumatra Province which experiences periodic flooding. The hydrological modeling was carried out in 2 scenarios: the existing condition and the redesign with the required parameters, including land topography, climate, and hydrology as input in the simulation. This hydrological modeling simulates the existing condition of drainage canals and the application of flood problem mitigation by making levee using HEC-RAS 2D. The simulation results show that flooding occurs due to the overflow of the Aek Sibirong River, which affects the condition of the drainage channel in plantation connected to the river. As Simulation, applying levee as high as 1.15 m to 3.45 m upstream and 1.10 m to 3 m downstream can overcome the overflow to prevent flooding in the plantation area.